A cross-sectional study on the association between vitamin D levels and caries in the permanent dentition of Korean children - In-Ja Kim; Heung-Soo Lee; Hyun-Jeong Ju; Ja-Young Na; Hyo-Won Oh (BMC, 2018)
Abstract Background A recent study in Canada reported that vitamin D deficiency is associated with dental caries. Because Koreans have been reported to be deficient in vitamin D, we investigated the relationship between dental caries and reduced serum vitamin D levels in Korean children. The purpose of this study was to analyze the relationships between blood vitamin D [25(OH)D] concentrations and dental caries in the permanent dentition of Korean children. Methods Data were collected from the Korea National Health and Nutrition Examination Survey performed in 2008-2013. A total of 1688 children (10-12 years of age) were enrolled. Vitamin D intake was measured through analysis of 25-hydroxy vitamin D [25(OH)D] levels. Caries experience in permanent dentition was assessed using the decay-missing-filled teeth (DMFT) index and decayed-missing-filled (DMF) rate. Statistical analyses included complex samples Chi-square tests, complex samples logistic regression analyses, and Pearson's correlations. Results The group with 25(OH) D levels lower than 50 nmol/L had a higher proportion of children with caries in the permanent dentition and permanent first molar than the group with 25(OH)D levels of 50 nmol/L or more. When external factors, such as sex, were controlled, 25(OH)D levels were not significantly correlated with caries, but were significantly correlated with first molar caries. Children with 25(OH)D levels lower than 50 nmol/L were 1.295 times more likely to have first molar caries than those with 25(OH)D levels of 50 nmol/L or more. Additionally, 25(OH)D levels and DMFT were negatively correlated; however, the degree of correlation was not strong. Conclusions The association between 25(OH)D and dental caries is still not clear. However, our findings suggested that vitamin D insufficiency may be a risk factor for dental caries.